PERAN PEMERINTAH DALAM PENATAAN DAN PENYELENGGARAAN TRANSPORTASI DI TERMINAL TIPE B BARUGA KENDARI - Nuhun, Ridwansyah; Soeparyanto, Try Sugiyarto; Nurrakhmad Arsyad, La Ode Muhamad; Fidmasari, Rezki; Satyadharma, Maudhy (Universitas Muhammadiyah Palembang, 2024)
This research aims to analyze the role that local governments should play in organizing transportation, especially in the arrangement, development and implementation of transportation operations in the Baruga Kendari Type B Passenger Terminal area. This research focuses on the role that the government should play in organizing the Baruga Kendari Type B Passenger Terminal. Data collection was carried out through interviews with relevant stakeholders at the Baruga Kendari Type B Passenger Terminal who were deemed to understand the issues raised. The results of the research found that the Southeast Sulawesi Provincial Government through the Department of Transportation has carried out roles in the implementation of land transportation, especially in the arrangement, development and implementation of operationalization in the Baruga Kendari Type B Passenger Terminal area in order to encourage the implementation of safe, comfortable, humane and sustainable transportation.